Infectious Diseases of Six Non-Domesticated Neo-Tropical Animals In Trinidad and Tobago - Kavita Ranjeeta Lall; Kegan Romelle Jones; Gary Wayne Garcia (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
This review serves to shed light on some common infectious diseases: their names, prevalence, site of infection and diagnostic tools for identificationof six (6) neo-tropical animals that are found in Trinidad and Tobago with the potential for domestication. These are theagouti(Dasyprocta leporina/ D. agouti), lappe/paca (Cuniculus paca/ Agouti paca), capybara (Hydrochoerus hydrochaeris), manicou/opossum (Didelphis marsupialis insularis), collared peccary (Tayassu tajacu/ Peccari tajucu) and red brocket deer (Mazama americana).There is over Ninety (90) references were used, with the earliest being 1951 and the most recent being in 2017.Where literature was lacking, information from other species within the same genus was incorporated and identified clearly. It was interesting to note that the majority of animals, despite being infected with pathogenic organisms were clinically healthy. In animals that showed clinical signs of disease there was a large quantity of pathogens present. This manuscript sheds some light on the pathogens that may use these animals as natural reservoirs. This review paper also includes many of the earliest identification of these pathogens in Neo-tropical animals in specific geographic regions.